1984
DOI: 10.1007/bf01255408
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in the effect of pargyline on dopamine concentrations in the rat hypophysis

Abstract: Dopamine concentrations were estimated in different regions of the infundibular-pituitary system of the rat. The highest values were found in the pituitary stalk where they are comparable to the concentrations in the striatum, and higher than in the median eminence. In the anterior lobe the dopamine (DA) concentrations of the upper pole (10% of the lobe tissue) were 2-5 times higher than in the rest of the lobe. Anterior lobe DA was significantly higher in rats about 6 months old than in rats about 3 months ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1985
1985
1990
1990

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 21 publications
(19 reference statements)
1
6
0
Order By: Relevance
“…These observations indi cate that the relatively low activity of the DA system in the NL can become activated in special endocrine states, when neurohormone secretion is maximally stimulated. A differ ence between the DA systems in NL and IL was also ob served in previous experiments in which an increase in tis sue DA content after inhibition of monoamine oxidase with pargyline occurred in the NL alone [14].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…These observations indi cate that the relatively low activity of the DA system in the NL can become activated in special endocrine states, when neurohormone secretion is maximally stimulated. A differ ence between the DA systems in NL and IL was also ob served in previous experiments in which an increase in tis sue DA content after inhibition of monoamine oxidase with pargyline occurred in the NL alone [14].…”
Section: Discussionmentioning
confidence: 92%
“…This calculation was considered to be valid because the experiments were carried out in paral lel on tissues from littermate rats. In previous experiments it has also been shown that more than 90% of IL tissue was removed by the method used [14], the NL and stalk ap peared microscopically intact, and the vasopressin release from isolated NLs prepared in this fashion was even larger than that from combined NILs [Racke et al, to be pub lished]. From table I it can be seen that for the control tis sues the evoked DA overflow from the ILs was apparently six times larger than that from the NLs.…”
Section: Da Releasementioning
confidence: 99%
“…In accord with these and other earlier studies, electrically evoked release of [3H]-NA from the neurohypophysis was effectively abolished by inclusion of 10"6 M tetrodotoxin during S; (S::S|, 0.023 ±0.006: n = 4) and is thus due to propagation of ac tion potentials into terminals. Dopamine is the major cat echolamine in the neurohypophysis, the dopamine content of the isolated neural lobe being some 3^4 times that of N A [27]. Uptake of ['F1]-NA.…”
Section: Na Releasementioning
confidence: 99%
“…However, our experiments suggest that the opioid peptides acting to modulate neurohormone secretion are derived from the neurohypophysis itself [I I]. We have thus perfor med the present studies on the neurohypophysis dissected free of intermediate lobe tissue, a procedure which also al lowed us to study output from NA terminals located exclu sively in the neurohypophysis [14,27], Here we investigated the action of endogenous opioids on electrically evoked re lease of OXT, AVP, and NA and the opioid receptor subtypes mediating these actions. In the accompanying paper [64] we have investigated the possible neuromodulatory actions of released NA on secretion from neurohor mone terminals.…”
mentioning
confidence: 99%
“…The neurohypophysis contains 1-2 pmol of NA (14], and NA is released upon depolarization of the nerve terminals in vitro [24]. We have used [3H]-NA prelabelling of NA stores to demonstrate release from NA terminals by electri cal stimulation [28].…”
Section: Opioid-na Interactions and Oxt Releasementioning
confidence: 99%